A glaze with imitation marble light feeling and its application in preparing ceramic tile with high fidelity imitation marble light feeling
By using raw materials such as potassium feldspar, quartz, talc, calcium borate, modified kaolin and composite matte materials, glaze with imitation marble light sense was prepared, which solved the problem of smooth glaze and low gloss in the prior art, and achieved high wear resistance and good light sense of ceramic tiles.
Patent Information
- Application Number
- CN202310426845.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-04-20
AI Technical Summary
The existing imitation marble tiles have the problem of mining non-renewable resources of natural ore, and it is difficult to take into account the effects of smooth glaze and low gloss, resulting in high production costs and uneven light sense.
The glaze with a marble-like light feeling is prepared by using raw materials such as potassium feldspar, quartz, talc, calcium borate, modified kaolin and composite matte materials through specific ratios and processes. Modified kaolin is modified by stearic acid and octadecyl trimethylammonium bromide to improve its dispersion and connection strength.
The glaze surface is smooth and delicate and low glossy, ensuring the wear resistance and good light sense of the tiles, and improving the hardness of the tiles.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic tile glazes, and in particular to a glaze with a marble-like light feeling and application of the glaze in preparing ceramic tiles with a high-fidelity marble-like light feeling. Background Art
[0002] The glaze applied to imitation marble tiles is generally made of natural ore. After grinding and adding water, it is applied to the surface of the body and melted by roasting at a certain temperature. When the temperature drops, a thin glass layer is formed on the surface of the ceramic. It increases the mechanical strength, thermal stability, and dielectric strength of the ceramic and prevents erosion by liquids and gases. It also increases the beauty of the tiles, makes them easy to clean, and prevents them from being stained by dust.
[0003] The natural minerals used in existing marble-like glazes are non-renewable resources. Long-term and large-scale mining is not conducive to long-term development. Moreover, the glazes either have a rough surface with low gloss or a smooth surface with high gloss. The two cannot be taken into account at the same time. There are also marble-like glazes with good light perception. On the basis of the original ordinary matte glaze, they add soft polishing equipment to softly polish the glaze. Although this soft polishing has low gloss, it greatly increases the production cost. There is also a soft glaze that sprays low-gloss ink on the high-gloss glaze. Although this process is simple to operate, the light perception of the tile surface is uneven. Summary of the invention
[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a glaze with imitation marble luster and its application in preparing ceramic tiles with high-fidelity imitation marble luster, so as to solve the problems raised in the above background technology.
[0005] The present invention solves the technical problem by adopting the following technical solution:
[0006] The present invention provides a glaze with a marble-like luster, comprising the following raw materials:
[0007] Potassium feldspar, quartz, talc, calcium borate, modified kaolin, composite matte material;
[0008] The specific formula includes the following raw materials: 20-50 parts of potassium feldspar, 20-50 parts of quartz, 5-10 parts of talc, 5-10 parts of calcium borate, 10-20 parts of modified kaolin and 8-15 parts of composite matte material.
[0009] Preferably, the glaze having a marble-like luster comprises the following raw materials:
[0010] 30 parts of potassium feldspar, 35 parts of quartz, 8 parts of talc, 8 parts of calcium borate, 16 parts of modified kaolin, and 12 parts of composite matte material.
[0011] Preferably, the preparation of the modified kaolin comprises the following steps:
[0012] S1, crushing kaolin into particles, then adding water and ball-milling until it passes through a 200-300 mesh sieve, and obtaining kaolin micropowder after airflow drying;
[0013] S2, adding 10-15 parts of stearic acid and 20-30 parts of octadecyltrimethylammonium bromide to 100-150 parts of kaolin powder by mass, and ultrasonically shaking for 10-15 minutes to obtain an ultrasonic mixed solution;
[0014] S3. Raise the temperature of the ultrasonic mixed solution to 70-80°C, then add 3-4 parts of tin crystal, 1-2 parts of white glass, 2-4 parts of magnesium oxide, and 1-3 parts of calcium carbonate in sequence and stir for 60-80 minutes, keep the temperature to react for 1-2 hours, and finally obtain modified kaolin after filtration, washing and drying.
[0015] Preferably, the mass of water added during ball milling is 8-10% of the kaolin, and the particle size of the kaolin after grinding is 0.1-0.3 μm.
[0016] Preferably, the mass percentage of silicon dioxide in the kaolin is 45-65%, and the mass percentage of aluminum oxide is 35-55%.
[0017] Preferably, the moisture content of the modified kaolin is less than 2%, wherein the content of particles with a particle size of 0.25-0.3 μm does not exceed 50%.
[0018] Preferably, the method for preparing the composite matte material comprises the following steps:
[0019] (1) Add barium oxide and manganese oxide into deionized water and disperse them uniformly at 2400 rpm to prepare a mixed solution with a mass concentration of 25%. Add sodium hydroxide solution dropwise into the mixed solution under stirring conditions to obtain a mixture A after reaction;
[0020] (2) Add mixture A into a constant temperature magnetic stirring water bath, heat to 75°C and then disperse at high speed for 10 hours, add methanol for precipitation, dry and grind to obtain a composite matte material.
[0021] Preferably, the composite matte material comprises the following raw materials in mass fractions: 20-30 parts of barium oxide, 10-30 parts of manganese oxide, 5-10 parts of methanol, and 100-200 parts of deionized water.
[0022] Preferably, the preparation of the marble-like light-sensitive glaze comprises the following steps:
[0023] Step 1: Grind potassium feldspar, quartz, talc, calcium borate, modified kaolin, and composite matte material and mix them evenly to obtain dry powder glaze;
[0024] Step 2: Mix the dry powder glaze with water in a weight ratio of 100:40-50 to obtain a marble-like glaze with a concentration of 40-50%;
[0025] Step 3: sinter the glaze at 135-1500°C for 8-10 hours to obtain a glaze with a marble-like luster.
[0026] The glaze with imitation marble gloss prepared by the present invention and its application in preparing ceramic tiles with imitation marble gloss with high fidelity, the dispersibility of kaolin in the glaze is improved after being modified by stearic acid and octadecyltrimethylammonium bromide, thereby enhancing the connection strength between the glaze components, so that the prepared ceramic tiles with imitation marble gloss have better hardness.
[0027] Compared with the existing prior art, the present invention has the following beneficial effects:
[0028] The present invention uses natural minerals as a matrix, and mixes with modified kaolin and composite matte material to prepare the glaze. The glaze prepared under a specific ratio improves the glossiness of the glaze surface, achieves the purpose of smooth and delicate glaze surface with low glossiness, and ensures good wear resistance and light perception. DETAILED DESCRIPTION
[0029] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention of this embodiment provides a glaze with a marble-like luster, comprising the following raw materials:
[0031] Potassium feldspar, quartz, talc, calcium borate, modified kaolin, composite matte material;
[0032] The specific formula includes the following raw materials: 20-50 parts of potassium feldspar, 20-50 parts of quartz, 5-10 parts of talc, 5-10 parts of calcium borate, 10-20 parts of modified kaolin and 8-15 parts of composite matte material.
[0033] The glaze with imitation marble luster of this embodiment includes the following raw materials:
[0034] 30 parts of potassium feldspar, 35 parts of quartz, 8 parts of talc, 8 parts of calcium borate, 16 parts of modified kaolin, and 12 parts of composite matte material.
[0035] The preparation of the modified kaolin of this embodiment comprises the following steps:
[0036] S1, crushing kaolin into particles, then adding water and ball-milling until it passes through a 200-300 mesh sieve, and obtaining kaolin micropowder after airflow drying;
[0037] S2, adding 10-15 parts of stearic acid and 20-30 parts of octadecyltrimethylammonium bromide to 100-150 parts of kaolin powder by mass, and ultrasonically shaking for 10-15 minutes to obtain an ultrasonic mixed solution;
[0038] S3. Raise the temperature of the ultrasonic mixed solution to 70-80°C, then add 3-4 parts of tin crystal, 1-2 parts of white glass, 2-4 parts of magnesium oxide, and 1-3 parts of calcium carbonate in sequence and stir for 60-80 minutes, keep the temperature to react for 1-2 hours, and finally obtain modified kaolin after filtration, washing and drying.
[0039] In this embodiment, the mass of water added during ball milling is 8-10% of the kaolin, and the particle size of the kaolin after grinding is 0.1-0.3 μm.
[0040] The mass percentage of silicon dioxide in the kaolin of this embodiment is 45-65%, and the mass percentage of aluminum oxide is 35-55%.
[0041] The moisture content of the modified kaolin in this embodiment is less than 2%, wherein the content of particles with a particle size of 0.25-0.3 μm does not exceed 50%.
[0042] The preparation method of the composite matte material of this embodiment comprises the following steps:
[0043] (1) Add barium oxide, manganese oxide and zinc oxide into deionized water and disperse them uniformly at 2400 rpm to prepare a mixed solution with a mass concentration of 25%. Add sodium hydroxide solution dropwise into the mixed solution under stirring conditions to obtain a mixture A after reaction;
[0044] (2) Add mixture A into a constant temperature magnetic stirring water bath, heat to 75°C and then disperse at high speed for 10 hours, add methanol for precipitation, dry and grind to obtain a composite matte material.
[0045] The composite matte material of this embodiment includes the following raw materials in mass fractions: 20-30 parts of barium oxide, 10-30 parts of manganese oxide, 10-20 parts of zinc oxide, 5-10 parts of methanol, and 100-200 parts of deionized water.
[0046] The preparation of the marble-like light-sensitive glaze of this embodiment includes the following steps:
[0047] Step 1: Grind potassium feldspar, quartz, talc, calcium borate, modified kaolin, and composite matte material and mix them evenly to obtain dry powder glaze;
[0048] Step 2: Mix the dry powder glaze with water in a weight ratio of 100:40-50 to obtain a marble-like glaze with a concentration of 40-50%;
[0049] Step 3: sinter the glaze at 1350°C-1500°C for 8-10 hours to obtain a glaze with a marble-like luster.
[0050] Example 1.
[0051] The present invention of this embodiment provides a glaze with a marble-like luster, comprising the following raw materials:
[0052] Potassium feldspar, quartz, talc, calcium borate, modified kaolin, composite matte material;
[0053] The specific formula includes the following raw materials: 20 parts of potassium feldspar, 20 parts of quartz, 5 parts of talc, 5 parts of calcium borate, 10 parts of modified kaolin, and 8 parts of composite matte material.
[0054] The preparation of the modified kaolin of this embodiment comprises the following steps:
[0055] S1, crushing kaolin into particles, then adding water and ball-milling until it passes through a 200-mesh sieve, and air-drying to obtain kaolin micropowder;
[0056] S2, adding 10 parts of stearic acid and 20 parts of octadecyltrimethylammonium bromide to 100 parts of kaolin powder by mass, and ultrasonically vibrating for 10 minutes to obtain an ultrasonic mixed solution;
[0057] S3. Raise the temperature of the ultrasonic mixed solution to 70°C, then add 3 parts of tin crystal, 1 part of white glass, 2 parts of magnesium oxide and 1 part of calcium carbonate in sequence and stir for 60 minutes. Keep the temperature to react for 1 hour, and finally obtain modified kaolin after filtration, washing and drying.
[0058] In this embodiment, the mass of water added during ball milling is 8% of the kaolin, and the particle size of the kaolin after grinding is 0.1 μm.
[0059] The mass percentage of silicon dioxide in the kaolin of this embodiment is 45%, and the mass percentage of aluminum oxide is 35%.
[0060] The moisture content of the modified kaolin in this embodiment is less than 2%, wherein the content of particles with a particle size of 0.25 μm does not exceed 50%.
[0061] The preparation method of the composite matte material of this embodiment comprises the following steps:
[0062] (1) Add barium oxide, manganese oxide and zinc oxide into deionized water and disperse them uniformly at 2400 rpm to prepare a mixed solution with a mass concentration of 25%. Add sodium hydroxide solution dropwise into the mixed solution under stirring conditions to obtain a mixture A after reaction;
[0063] (2) Add mixture A into a constant temperature magnetic stirring water bath, heat to 75°C and then disperse at high speed for 10 hours, add methanol for precipitation, dry and grind to obtain a composite matte material.
[0064] The composite matte material of this embodiment includes the following raw materials in mass fractions: 20 parts of barium oxide, 10 parts of manganese oxide, 10 parts of zinc oxide, 5 parts of methanol, and 100 parts of deionized water.
[0065] The preparation of the marble-like light-sensitive glaze of this embodiment includes the following steps:
[0066] Step 1: Grind potassium feldspar, quartz, talc, calcium borate, modified kaolin, and composite matte material and mix them evenly to obtain dry powder glaze;
[0067] Step 2: Mix the dry powder glaze with water in a weight ratio of 100:40 to obtain a glaze with a concentration of 40% imitating marble gloss;
[0068] Step 3: sinter the glaze at 1350°C for 8 hours to obtain a glaze that imitates marble luster.
[0069] Example 2.
[0070] The present invention of this embodiment provides a glaze with a marble-like luster, comprising the following raw materials:
[0071] Potassium feldspar, quartz, talc, calcium borate, modified kaolin, composite matte material;
[0072] The specific formula includes the following raw materials: 33 parts of potassium feldspar, 35 parts of quartz, 8 parts of talc, 8 parts of calcium borate, 16 parts of modified kaolin, and 12 parts of composite matte material.
[0073] The preparation of the modified kaolin of this embodiment comprises the following steps:
[0074] S1, crushing kaolin into particles, then adding water and ball-milling until it passes through a 260-mesh sieve, and air-drying to obtain kaolin micropowder;
[0075] S2, adding 113 parts of stearic acid and 25 parts of octadecyltrimethylammonium bromide to 130 parts of kaolin powder by mass, and ultrasonically vibrating for 12 minutes to obtain an ultrasonic mixed solution;
[0076] S3. Raise the temperature of the ultrasonic mixed solution to 76°C, then add 3 parts of tin crystal, 1 part of white glass, 3 parts of magnesium oxide and 2 parts of calcium carbonate in sequence and stir for 70 minutes. Keep the temperature to react for 1.5 hours, and finally obtain modified kaolin after filtration, washing and drying.
[0077] In this embodiment, the mass of water added during ball milling is 9% of the kaolin, and the particle size of the kaolin after grinding is 0.2 μm.
[0078] The mass percentage of silicon dioxide in the kaolin of this embodiment is 50%, and the mass percentage of aluminum oxide is 45%.
[0079] The moisture content of the modified kaolin in this embodiment is less than 2%, wherein the content of particles with a particle size of 0.27 μm does not exceed 50%.
[0080] The preparation method of the composite matte material of this embodiment comprises the following steps:
[0081] (1) Add barium oxide, manganese oxide and zinc oxide into deionized water and disperse them uniformly at 2400 rpm to prepare a mixed solution with a mass concentration of 25%. Add sodium hydroxide solution dropwise into the mixed solution under stirring conditions to obtain a mixture A after reaction;
[0082] (2) Add mixture A into a constant temperature magnetic stirring water bath, heat to 75°C and then disperse at high speed for 10 hours, add methanol for precipitation, dry and grind to obtain a composite matte material.
[0083] The composite matte material of this embodiment includes the following raw materials in mass fractions: 25 parts of barium oxide, 20 parts of manganese oxide, 15 parts of zinc oxide, 8 parts of methanol, and 150 parts of deionized water.
[0084] The preparation of the marble-like light-sensitive glaze of this embodiment includes the following steps:
[0085] Step 1: Grind potassium feldspar, quartz, talc, calcium borate, modified kaolin, and composite matte material and mix them evenly to obtain dry powder glaze;
[0086] Step 2: Mix the dry powder glaze with water in a weight ratio of 100:45 to obtain a glaze with a concentration of 45% imitating marble gloss;
[0087] Step 3: sinter the glaze at 1400°C for 9 hours to obtain a glaze with a marble-like luster.
[0088] Example 3.
[0089] The present invention of this embodiment provides a glaze with a marble-like luster, comprising the following raw materials:
[0090] Potassium feldspar, quartz, talc, calcium borate, modified kaolin, composite matte material;
[0091] The specific formula includes the following raw materials: 50 parts of potassium feldspar, 50 parts of quartz, 10 parts of talc, 10 parts of calcium borate, 20 parts of modified kaolin, and 15 parts of composite matte material.
[0092] The preparation of the modified kaolin of this embodiment comprises the following steps:
[0093] S1, crushing kaolin into particles, then adding water and ball-milling until it passes through a 300-mesh sieve, and air-drying to obtain kaolin micropowder;
[0094] S2, adding 15 parts of stearic acid and 30 parts of octadecyltrimethylammonium bromide to 150 parts of kaolin powder by mass, and ultrasonically vibrating for 15 minutes to obtain an ultrasonic mixed solution;
[0095] S3. Raise the temperature of the ultrasonic mixed solution to 80°C, then add 4 parts of tin crystal, 2 parts of white glass, 4 parts of magnesium oxide and 3 parts of calcium carbonate in sequence and stir for 80 minutes. Keep the temperature to react for 2 hours, and finally obtain modified kaolin after filtration, washing and drying.
[0096] In this embodiment, the mass of water added during ball milling is 10% of the kaolin, and the particle size of the kaolin after grinding is 0.3 μm.
[0097] The mass percentage of silicon dioxide in the kaolin of this embodiment is 65%, and the mass percentage of aluminum oxide is 55%.
[0098] The moisture content of the modified kaolin in this embodiment is less than 2%, wherein the content of particles with a particle size of 0.3 μm does not exceed 50%.
[0099] The preparation method of the composite matte material of this embodiment comprises the following steps:
[0100] (1) Add barium oxide, manganese oxide and zinc oxide into deionized water and disperse them uniformly at 2400 rpm to prepare a mixed solution with a mass concentration of 25%. Add sodium hydroxide solution dropwise into the mixed solution under stirring conditions to obtain a mixture A after reaction;
[0101] (2) Add mixture A into a constant temperature magnetic stirring water bath, heat to 75°C and then disperse at high speed for 10 hours, add methanol for precipitation, dry and grind to obtain a composite matte material.
[0102] The composite matte material of this embodiment includes the following raw materials in mass fractions: 30 parts of barium oxide, 30 parts of manganese oxide, 20 parts of zinc oxide, 10 parts of methanol, and 200 parts of deionized water.
[0103] The preparation of the marble-like light-sensitive glaze of this embodiment includes the following steps:
[0104] Step 1: Grind potassium feldspar, quartz, talc, calcium borate, modified kaolin, and composite matte material and mix them evenly to obtain dry powder glaze;
[0105] Step 2: Mix the dry powder glaze with water in a weight ratio of 100:50 to obtain a glaze with a concentration of 50% imitating marble gloss;
[0106] Step 3: sinter the glaze at 1500°C for 10 hours to obtain a glaze with a marble-like luster.
[0107] Comparative Example 1.
[0108] The difference from Example 3 is that the kaolin is not modified.
[0109] Comparative Example 2.
[0110] The difference from Example 3 is that no composite matte material is added during the preparation of the glaze.
[0111] Comparative Example 3.
[0112] The difference from Example 3 is that excess amounts of barium oxide and manganese oxide are added to the composite matte material.
[0113] The products of Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests;
[0114] 30 glaze samples were prepared and divided into 6 groups with 5 samples in each group. Each group corresponded to Examples 1-3 and Comparative Examples 1-3 and were numbered A / B / C / D / E / F. The glazes were applied on the surface of ceramic tiles. After high-temperature firing, the glaze samples of groups A / B / C / D / E / F were tested respectively. The test results are shown in the following table.
[0115]
[0116] It can be seen from Examples 1-3 that the glaze with imitation marble luster made by the present invention and its application in the preparation of ceramic tiles with high-fidelity imitation marble luster is prepared by mixing natural minerals with modified kaolin and composite matte materials. The glaze prepared under a specific ratio improves the glossiness of the glaze surface, achieving the purpose of smooth and delicate glaze surface with low glossiness.
[0117] It can be seen from Comparative Example 1 and Example 3 that the dispersibility of the kaolin in the glaze is improved after being modified with stearic acid and octadecyltrimethylammonium bromide, thereby enhancing the connection strength between the glaze components and improving the hardness of the glaze;
[0118] In addition, it was found from Comparative Examples 2-3 that in the preparation of glazes with imitation marble luster and their use in the preparation of ceramic tiles with highly realistic imitation marble luster, the excessive addition of barium oxide and manganese oxide in the composite matte material reduced the transparency of the glaze, distorted the texture of the glaze surface, and the glossiness of the glaze was higher.
[0119] The innovation of the present invention is:
[0120] The present invention uses natural minerals as a matrix, and mixes them with modified kaolin and a composite matte material to prepare a glaze prepared under a specific ratio, which improves the glossiness of the glaze surface, achieves the purpose of a smooth and delicate glaze surface with low glossiness, and ensures good wear resistance and light perception. At the same time, the dispersibility of the kaolin in the glaze is improved after being modified with stearic acid and octadecyltrimethylammonium bromide, thereby enhancing the connection strength between the glaze components, so that the hardness of the prepared tile with imitation marble light perception is better.
[0121] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
[0122] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A glaze with a marble-like luster, characterized in that: Including the following raw materials: potassium feldspar, quartz, talc, calcium borate, modified kaolin, composite matte material; The specific formula includes the following raw materials: 20-50 parts of potassium feldspar, 20-50 parts of quartz, 5-10 parts of talc, 5-10 parts of calcium borate, 10-20 parts of modified kaolin, and 8-15 parts of composite matte material; The preparation of the modified kaolin comprises the following steps: S1, crushing kaolin into particles, then adding water and ball-milling until it passes through a 200-300 mesh sieve, and obtaining kaolin micropowder after airflow drying; S2, adding 10-15 parts of stearic acid and 20-30 parts of octadecyltrimethylammonium bromide to 100-150 parts of kaolin powder by mass, and ultrasonically shaking for 10-15 minutes to obtain an ultrasonic mixed solution; S3, heating the ultrasonic mixed solution to 70-80°C, then sequentially adding 3-4 parts of tin crystal material, 1-2 parts of white glass, 2-4 parts of magnesium oxide, and 1-3 parts of calcium carbonate and stirring for 60-80 minutes, keeping the temperature for reaction for 1-2 hours, and finally filtering, washing, and drying to obtain modified kaolin; The preparation method of the composite matte material comprises the following steps: (1) Add barium oxide and manganese oxide into deionized water and disperse them uniformly at 2400 rpm to prepare a mixed solution with a mass concentration of 25%. Add sodium hydroxide solution dropwise into the mixed solution under stirring conditions to obtain a mixture A after reaction; (2) Add mixture A into a constant temperature magnetic stirring water bath, heat to 75°C and then disperse at high speed for 10 hours, add methanol for precipitation, dry and grind to obtain a composite matte material.
2. The glaze with imitation marble luster according to claim 1, characterized in that: Including the following ingredients: 30 parts of potassium feldspar, 35 parts of quartz, 8 parts of talc, 8 parts of calcium borate, 16 parts of modified kaolin, and 12 parts of composite matte material.
3. The glaze with imitation marble luster according to claim 1, characterized in that: The mass of water added during ball milling is 8-10% of the kaolin, and the particle size of the kaolin after grinding is 0.1-0.3 μm.
4. The glaze with imitation marble luster according to claim 1, characterized in that: The mass percentage of silicon dioxide in the kaolin is 45-65%, and the mass percentage of aluminum oxide is 35-55%.
5. The glaze with imitation marble luster according to claim 1, characterized in that: The moisture content of the modified kaolin is less than 2%, wherein the content of particles with a particle size of 0.25-0.3 μm does not exceed 50%.
6. The glaze with imitation marble luster according to claim 1, characterized in that: The preparation method of the composite matte material comprises the following raw materials in mass fractions: 20-30 parts of barium oxide, 10-30 parts of manganese oxide, 5-10 parts of methanol, and 100-200 parts of deionized water.
7. The glaze with imitation marble luster according to claim 1, characterized in that: The preparation of the marble-like light-sensitive glaze comprises the following steps: Step 1: Grind potassium feldspar, quartz, talc, calcium borate, modified kaolin, and composite matte material and mix them evenly to obtain dry powder glaze; Step 2: Mix the dry powder glaze with water in a weight ratio of 100:40-50 to obtain a marble-like glaze with a concentration of 40-50%; Step 3: sinter the glaze at 135-1500°C for 8-10 hours to obtain a glaze with a marble-like luster.
8. Use of the glaze with imitation marble luster as claimed in any one of claims 1 to 7 in preparing ceramic tiles with high fidelity imitation marble luster.
Citation Information
Patent Citations
Simulated marble glaze, ceramic product with simulated marble glaze and preparation method
CN107352797A